Criteria to define interruption of transmission of human cytomegalovirus from organ donor to recipient. (17th November 2017) - Baraniak, Ilona Anna; Reeves, Matthew B.; Griffiths, Paul D.
Summary: In this review article, we consider results suggesting that transmission of human cytomegalovirus (HCMV) from a donor of a solid organ to an immunologically naive individual can be reduced. Two randomized controlled trials have been conducted recently, one of active immunization of recipients pretransplant and another of passive immunization with monoclonal antibodies specific for HCMV given at the time of transplant. Although the available data are encouraging—providing evidence of a reduction in the incidence of HCMV viraemia—they fall short of what would be required to prove definitively that transmission has been completely prevented. Here, we reflect on these studies and propose a set of 5 criteria, which, if satisfied in the future, could be taken as proof that active and/or passive immunization against HCMV effectively interrupts transmission of virus from the donor. We suggest that these criteria are considered when designing future randomized controlled trials.